Pengaruh Behavioral Intention dan User Behavioral terhadap Gender sebagai Variabel Moderasi - Julyazti, Nadya Fritanita; Alfarisi, Mohamad Fany; Adrianto, Fajri (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to prove the effect of performance expectancy, effort expectancy, social influence and facilitating conditions on the behavioral intention of customers in the city of Padang to use Islamic banking mobile banking in the city of Padang. In addition, this study aims to prove the role of gender as a moderator of the relationship between behavioral intention and customer user behavior. Using sharia banking mobile banking services in the city of Padang. Data collection was carried out by distributing questionnaires which were carried out directly or using the Google form. The data analysis method was carried out using the Structural Equation Model. Based on the results of hypothesis testing, it was found that performance expectancy, social influence, facilitating conditions had a significant effect on behavioral intention, besides that it was also found that gender did not moderate the relationship between behavioral intention and user behavior of customers using Islamic banking mobile banking services in Padang City.